MENINGKATKAN KETERAMPILAN BERBICARA MELALUI PROBLEM-BASED LEARNING DAN SNAKES AND LADDERS - Erawati, Galuh Agliesta; Aimah, Siti; Rulik, Margaretha (Journal of Lesson Study in Teacher Education, 2024)
This study aims to enhance the English speaking skills of 12th-grade students at SMA N 15 Semarang on the topic of social media effects through the Problem-Based Learning (PBL) model combined with the Snakes and Ladders game. Conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages, the study showed significant improvements. The average speaking score increased from 63 in the pre-test to 72 in Cycle I, and further to 75 in Cycle II. Additionally, students achieving the minimum passing grade (KKM) rose from 60% in Cycle I to 80% in Cycle II. The interactive approach of PBL and Snakes and Ladders fostered active participation and confidence, demonstrating the effectiveness of integrating games and problem-solving strategies to improve engagement and speaking proficiency.